Is this the past? The place of role-play exercises in undergraduate history teaching - Beidatsch, Cedric; Broomhall, Susan (Journal of University Teaching and Learning Practice, 2010)
Increasingly, academic teachers are exploring the learning opportunities offered by student-centred participatory classroom and web-supported exercises. Role-play and gaming activities have been highlighted as fora which provide development of a range of personal and social skill sets in students, as well as understanding of subject content. This paper reports on research exploring how such exercises in an undergraduate history unit can be used to deliver core historical content and generic skills, and to develop students’ knowledge of the professional historian’s craft and historiographical practice.